2017
DOI: 10.1016/s2352-3018(16)30224-7
|View full text |Cite
|
Sign up to set email alerts
|

From HIV infection to therapeutic response: a population-based longitudinal HIV cascade-of-care study in KwaZulu-Natal, South Africa

Abstract: Summary Background Standard approaches to estimation of losses in the HIV cascade of care are typically cross-sectional and do not include the population stages before linkage to clinical care. We used indiviual-level longitudinal cascade data, transition by transition, including population stages, both to identify the health-system losses in the cascade and to show the differences in inference between standard methods and the longitudinal approach. Methods We used non-parametric survival analysis to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 30 publications
4
88
0
Order By: Relevance
“…Other discrepancies and the wide range of estimates of the first 90 might be due to large regional differences in testing uptake; although national and regional data in this case are similar. Nonetheless, our findings contribute to growing evidence that diagnosis remains a major barrier to achieving 90-90-90 [32] and to the increasing consensus that given the large disparity in knowledge of status among men, who test less frequently and who have poorer HIV outcomes over the lifecourse as compared to women [33]; new programming must creatively target men [9,34,35]. Our findings regarding the second 90 target, "on ART, " that 88.6% of men and 92.4% of women with known status are on treatment, are higher than similar surveys [27,28] and national estimates [5].…”
Section: Discussionsupporting
confidence: 54%
“…Other discrepancies and the wide range of estimates of the first 90 might be due to large regional differences in testing uptake; although national and regional data in this case are similar. Nonetheless, our findings contribute to growing evidence that diagnosis remains a major barrier to achieving 90-90-90 [32] and to the increasing consensus that given the large disparity in knowledge of status among men, who test less frequently and who have poorer HIV outcomes over the lifecourse as compared to women [33]; new programming must creatively target men [9,34,35]. Our findings regarding the second 90 target, "on ART, " that 88.6% of men and 92.4% of women with known status are on treatment, are higher than similar surveys [27,28] and national estimates [5].…”
Section: Discussionsupporting
confidence: 54%
“…A recent longitudinal study found that only 45% of HIV-positive individuals are linked into care (Haber et al 2017), and our study recruited those who made this critical link, in which positive relationship dynamics may have played a role. In addition, because we did not recruit participants based on couple HIV status, our sample consisted primarily of seroconcordant HIV-positive couples who were more likely to self-select to enrol in the study (e.g., couples who are discordant may be more likely to be broken up or less stable).…”
Section: Discussionmentioning
confidence: 99%
“…Haber et al used a similar approach, summarizing the distribution of the population 2 years after enrollment [29]. A strength McNairy's and our approach is that both consider outcomes of patients who do not initiate ART.…”
Section: Appendix Figurementioning
confidence: 99%